Jonathan Bolton, Worlds of Dissent: Charter 77, The Plastic People of the Universe, and Czech Culture under Communism: Cambridge (Mass.) 2012, Harvard University Press, 352 s. - Feinberg , Joseph Grim (Dějiny – teorie – kritika, 2013)
Review.